Construction of TiO2 microsphere through different titanium precursors via a green pathway - Lin Guo; Huimin Gao; Kecheng Liu; Yanhua Ding; Xin Li; Haiquan Xie (Results in Chemistry, 2022)
TiO2 microspheres (TMCS) with superior dispersity and uniform particle size (size distribution vary from 1 µm to 3 µm) were synthesized by using of different titanium precursors through a sol–gel method. Scanning electron microscopy (SEM) and Transmission electron microscopy (TEM) were employed to study the morphology and microstructure. Moreover, by Brunauer-Emmett-Teller (BET) test, the specific surface area of TMCS were about 200 m2/g. In addition, Raman spectroscopy (Raman), X-ray diffraction (XRD) and X–ray photo-electron spectroscopy (XPS) were applied to investigate the phase composition and existing state of TMCS. Furthermore, its photocatalytic activity was estimated by observing the degradation efficiency of Rhodamine (RhB). Remarkably, the degradation efficiency is 98 % after 30 min and the photocatalytic degradation rate remained almost unchanged in five successive cycles, indicating that TMCS were stable and suitable for removing RhB in water. Finally, the probable formation mechanism of TMCS was studied. The spontaneous aggregation of TiO2 nanoparticles lead to the formation of TMCS which would be promoted to combine with others to form mesoporous TMCS by temperature. Therefore, this work provides an encouraging pathway for controlling the morphology of TiO2 and showing potential application in wastewater treatment.